Determining wind energy resources in Turkmenistan - K. A. Saryyev (Известия высших учебных заведений: Проблемы энергетики, 2021)
THE PURPOSE. Studying the complex issues associated with providing consumers who are away from the central power supply system with environmentally safe renewable energy source, i.e. conversion of wind energy into electrical energy and uninterrupted supply of electricity to consumers. In this area, one of the complex issues is to determine the wind energy resources in the area where it is planned to install a wind farm.The article deals with the determination of wind energy resources in Turkmenistan. Using databases obtained from meteorological stations over several years, calculations of wind energy resources by region are carried out. This will quickly and in detail analyze the wind energy potential in a particular area to assess the choice of capacity of the projected wind turbines, with the aim of ensuring sustainable development of the region and the reliability of electricity supply.METHODS. In order to estimate the wind energy resources in the area it is necessary to determine the average wind speed per year. In this research work the average annual wind speeds obtained from meteorological stations installed in different regions of Turkmenistan were used. These data were compared with the actual data obtained from the 2 kW wind power plant installed at the research site of the State Energy institute of Turkmenistan and the relevant graphs were built. The results of the obtained data can be used for optimal selection of wind power plant locations and assessment of wind energy resources of the region. RESULTS.As a result of the calculations, wind energy reserves in the region and for the regions of Turkmenistan were determined, as well as the optimal locations of wind farms.Using the technical characteristics of a 2kW wind power plant, the average annual electricity output of a wind power plant of different capacity is determined.With the correct definition of wind energy potential, there is an opportunity to solve energy, economic, environmental and social issues of the country. And also there is an opportunity to mitigate climate change on the basis of wind energy installations, and their resources, environmental benefits, goals and objectives on the scientific methodological basis in the field of wind energy for implementation of state programs for energy conservation in Turkmenistan and energy supply of the region.CONCLUSIONS. On the basis of the carried out scientific work the wind energy resources and technical potentials of wind power plants in the territory of Turkmenistan were determined and the database for compiling the wind energy cadastre was created.